2017
DOI: 10.1186/s12974-017-0796-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 as a mediator of fatigue in disease: a narrative review

Abstract: Fatigue is commonly reported in a variety of illnesses, and it has major impact on quality of life. Previously, it was thought that fatigue originates in the skeletal muscles, leading to cessation of activity. However, more recently, it has become clear that the brain is the central regulator of fatigue perception. It has been suggested that pro-inflammatory cytokines, especially interleukin-1 alpha (IL-1α) and interleukin-1 beta (IL-1β), play a prominent role in the development of central fatigue, and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 147 publications
(146 reference statements)
0
40
0
2
Order By: Relevance
“…Due to this metabolic switch, iMφs are very reliant on surrounding glucose concentrations for survival and function, which they insure by inducing insulin resistance via IL-1β and TNF-αin adjacent stromal cells, thereby decreasing their competing glucose consumption  (Medzhitov, 2008;Shoelson et al, 2006). The release of inflammatory cytokines in microscopic injuries of our skin and mucosae that characterize our daily life does not cause symptoms, but they are at the origin of the cardinal features of inflammation in bigger localized-(calor, dolor, rubor, tumor (Nathan, 2002)) and systemic-(sleepiness (Roerink et al, 2017), fever, hyperglycemia (McGuinness, 2005)) infections and can participate in shock and organ failure if the infection gets out of hand.…”
Section: Inflammation a Crucial Process For Survivalmentioning
confidence: 99%
“…Due to this metabolic switch, iMφs are very reliant on surrounding glucose concentrations for survival and function, which they insure by inducing insulin resistance via IL-1β and TNF-αin adjacent stromal cells, thereby decreasing their competing glucose consumption  (Medzhitov, 2008;Shoelson et al, 2006). The release of inflammatory cytokines in microscopic injuries of our skin and mucosae that characterize our daily life does not cause symptoms, but they are at the origin of the cardinal features of inflammation in bigger localized-(calor, dolor, rubor, tumor (Nathan, 2002)) and systemic-(sleepiness (Roerink et al, 2017), fever, hyperglycemia (McGuinness, 2005)) infections and can participate in shock and organ failure if the infection gets out of hand.…”
Section: Inflammation a Crucial Process For Survivalmentioning
confidence: 99%
“…In this study, cytokine profiles of female CFS/ME patients participating in a randomized controlled trial on the effect of IL-1 inhibition on fatigue severity [ 22 ] were compared with age- and gender-matched healthy neighborhood controls. The rationale of this RCT was that IL-1—despite the fact that it is notoriously difficult to measure in the circulation—may play a pathophysiological role in CFS, and its activity may be confined to the brain compartment [ 23 ]. In addition to the cytokines included in the PEA platform, TGF-β and the IL-1 receptor antagonist (IL1-Ra), were measured separately using an ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging studies showed disturbed connectivity in prefrontal cortex and frontal networks in these patients (19,20), as well as impaired glutamate levels in this brain area [133,134]. On the other hand, regarding cytokines, several investigators have measured these markers levels in the blood of CFS patients, and interesting associations between IL-1 and other cytokine levels and fatigue symptoms have been reported [24].…”
Section: Evidence Of Microglial Activation and Pro-inflammatory Cytokmentioning
confidence: 91%
“…Since the CNS may be a key site underlying prolonged fatigue symptoms, studies have also evaluated cytokine levels in the cerebrospinal fluid. While two studies found no significant differences in cytokine levels in cerebrospinal fluid between patients and controls [144,145], another study reported lower IL-1β and IL-1Ra concentrations in the cerebrospinal fluid of CFS patients compared to multiple sclerosis and control groups [146], pointing to abnormalities in this cytokine signaling in the CNS [24]. In this context, Jokela et al, 2016 provides a consistent evidence for the link between systemic inflammation and fatigue/somatic symptoms in depression.…”
Section: Evidence Of Microglial Activation and Pro-inflammatory Cytokmentioning
confidence: 98%
See 1 more Smart Citation